Audit Tenure, Audit Independence, Audit Committee Independence, Board Independence, and Audit Quality in the Listed Deposit Money Banks in Nigeria: The Moderating Effect of Institutional Ownership - Haruna, Saratu Yakubu; Bala, Hussaini; Bello, Muhammad Sani (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
The study examined the moderating effect of institutional ownership on relationship between audit tenure, audit independence, board independence and audit quality of listed deposit money banks (LDMBs) in Nigeria. The study population comprises 14 LDMBs on the Nigerian Stock Exchange as at 31st December, 2020. 13 LDMBs were used as sample of the study. Logit regression technique was used as a tool of data analysis. Findings of the study revealed that, in the direct relationship, audit independence, board independence and institutional ownership have significant effect on the audit quality of LDMBs in Nigeria. The finding of the moderated model of the study reveals that institutional ownership has a significant negative moderating role on the relationship between audit tenure, audit independence, board independence and audit quality of LDMBs. It is therefore recommended among others that listed deposit money banks in Nigeria should ensure that they consider long-term institutional shareholding since those with a long-term stake have the motivation to monitor management and thereby, requesting a better audit quality through BIG4 auditors.